Análisis del dimensionamiento de una estación de recarga renovable fotolinera ubicada en la ciudad de Saraguro - Armijos Mora, Galo Alfonso (2024)
The objective of this document is to analyze the sizing process of a photovoltaic station in the city of Saraguro. For this purpose, a thorough study of the main variables and factors involved in the implementation of an electric vehicle charging station using solar photovoltaic energy has been carried out. After analyzing and synthesizing the relevant information, in order to acquire the necessary knowledge about the different types of existing charging stations, the location has been studied taking into account determining factors such as geographical, environmental and economic factors, to determine whether it is the right place for an energy study. Given this, for the sizing of the photovoltaic (PV) system, the following factors were considered: the battery capacity of the Kia Soul electric vehicle (EV), the existing irradiation at the site, the nominal voltage of the system and the elements available on the market. Since it is a magna charge and considering that it is a system isolated from the grid, there are no suitable components, which generated the search for practical solutions. The most viable solution was to create four "small" SF, based on the power of the current inverter that was available on the market, in such a way that by connecting them to a general connection bar, they would be able to supply a power of 40 kW and charge the EV battery in 3 hours. Keywords: Photovoltaic station, charging station, solar panels, off-grid photovoltaic systems.